Genome Sequencing for Genetics Diagnosis of Patients With Intellectual Disability: The DEFIDIAG Study - Binquet, Christine; Lejeune, Catherine; Faivre, Laurence; Bouctot, Marion; Asensio, Marie-Laure; Simon, Alban; Deleuze, Jean-François; Boland, Anne; Guillemin, Francis; Seror, Valérie; Delmas, Christelle; Espérou, Hélène; et al. (Frontiers in Genetics, 2022)
Introduction: Intellectual Disability (ID) is the most common cause of referral to pediatric genetic centers, as it affects around 1%-3% of the general population and is characterized by a wide genetic heterogeneity. The Genome Sequencing (GS) approach is expected to achieve a higher diagnostic yield than exome sequencing given its wider and more homogenous coverage, and, since theoretically, it can more accurately detect variations in regions traditionally not well captured and identify structural variants, or intergenic/deep intronic putatively pathological events. The decreasing cost of sequencing, the progress in data-management and bioinformatics, prompted us to assess GS efficiency as the first line procedure to identify the molecular diagnosis in patients without obvious ID etiology. This work is being carried out in the framework of the national French initiative for genomic medicine (Plan France Médecine Génomique 2025). Methods and Analysis: This multidisciplinary, prospective diagnostic study will compare the diagnostic yield of GS trio analysis (index case, father, mother) with the French core minimal reference strategy (Fragile-X testing, chromosomal microarray analysis and Gene Panel Strategy of 44 selected ID genes). Both strategies are applied in a blinded fashion, in parallel, in the same population of 1275 ID index cases with no obvious diagnosis (50% not previously investigated). Among them, a subgroup of 196 patients are randomized to undergo GS proband analysis in addition to GS trio analysis plus the French core minimal reference strategy, in order to compare their efficiency. The study also aims to identify the most appropriate strategy according to the clinical presentation of the patients, to evaluate the impact of deployment of GS on the families’ diagnostic odyssey and the modification of their care, and to identify the advantages/difficulties for the patients and their families. Ethics Statement: The protocol was approved by the Ethics Committee Sud Méditerranée I and the French data privacy commission (CNIL, authorization 919361). Trial Registration: ClinicalTrials.gov identifier NCT04154891 (07/11/2019)